Percepções de docentes e discentes sobre a utilização de recursos didáticos nas disciplinas de práticas de ensino em Física na Universidade Federal do Amazonas - Gil, Antonio Xavier (2016)
This work of research leave of the following scientific problem: “What are the perceptions of teacher and students about the utilization of teaching didactic recourse in the discipline of teaching practices of Physic from UFAM that to be able modify the process of teachinglearning?”, and defend the argument that “The perceptions of teachers and students about didactic recourses in the teaching of Physic can modify the methodology that are utilized in the classroom”, in the way search for delineation, implementation, and verification of a methodology of teaching how a proposal for disciplines of teaching practices of physic from UFAM. And then, has as general objective “analyze the perceptions of the teachers and students about the utilization of the didactic recourse to construct a proposal of the physic teaching. For that, the research was divided in three parts. In the first part we have an initial scan with bibliography research, documental research, and application of interview with the teacher and questioner with the students for that through this perceptual analyses we can building a methodology to applied it in the second part as observation into the classroom, interview with teacher and focal group with students, whose perceptual data will be analyzing in the third part through analyze of content, employing of likert scale and perceptual maps. Therefore, the results obtained in the first stage were: The beginning perceptual map, the schedule of new organization of teaching planning and its news formulation; and in the second stage were: the construction of two teaching planning to apply into the classroom, the final perceptual map and its analysis; and the third stage were: the triangulation of data of the two perceptual maps, initial and final, and its analysis that become possible to give answers the ours researches questions, ours scientific problem, and the confirmation of what we defending as argument of thesis, permitting for us propose a model of the applied how didactics recourses to work the physic teaching in the classroom.